Estimated Health Care Utilization and Expenditures in Individuals With Heart Failure From the Medical Expenditure Panel Survey. (May 2021) - Klein, Sharon; Jiang, Shangqing; Morey, Jacob R.; Pai, Akila; Mancini, Donna M.; Lala, Anuradha; Ferket, Bart S.
Abstract : Background: Heart failure (HF) constitutes a growing burden for public health and the US health care system. While the prevalence of HF is increasing, differences in health care utilization and expenditures within various sociodemographic groups remain poorly defined. Methods: We used the Medical Expenditure Panel Survey to assess annual health care utilization and expenditures from 2012 to 2017. Health care utilization was based on the annual frequency of various health care encounters. Annual total and out-of-pocket expenditures were evaluated for hospital inpatient stays, emergency room visits, outpatient visits, office-based medical provider visits, prescribed medicines, dental visits, home health aid visits, and other medical expenses. We performed univariable and multivariable regression analysis based on patient characteristics including sociodemographic and comorbidity variables. Results: Our results showed that total health care expenditures among patients with HF were 21 177 (95% CI, 18 819–24 736) per year as compared with 5652 (95% CI, 5469–5837) in those without HF ( P <0.001). Total expenditures within the population with HF were primarily being driven by expenditures associated with inpatient hospitalizations. Increasing number of comorbid conditions was associated with significant increases in total health care expenditures. Older age, female sex, earlier study years, number of comorbidities, higher level of education, and increasing family income brackets independently raised out-of-pocket expenditures. Conclusions: Our findings of increased health care utilization and expenditures based on sex, age, increasing number of comorbidities, wealthier income status, and increased education attainment level may be used for efforts aimed at better distributing health care resources to improve health outcomes in HF. Abstract : Supplemental Digital Content is available in the text.